Perceiving statistical knowledge through digital apps: an exploratory study / Az’lina Abdul Hadi... [et al.] - Abdul Hadi, Az’lina; Mohd Yusop, Noorezatty; Mohd Razali, Nornadiah; Khairudin, Zuraida; Mohd Razali, Noraziah (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Statistics plays a vital role in various spheres of life. Choosing the right statistical analysis is one of the most crucial aspects in statistics. Some researchers especially those who have minimal statistical background, are often having difficulties in choosing the right statistical analysis for their study. Inappropriate analysis may produce misleading results at the end of the study. Hence, mySTATS Tracker was created as an alternative tool to assist the researcher in determining the right statistical analysis. The aim of this study was to gauge the effectiveness of using mySTATS Tracker in identifying the most appropriate statistical analysis based on the supplied input. In addition, this study intended to determine whether there was significant difference in score based on gender and faculties. The difference in the perception towards the usefulness and effectiveness of this application based on faculties was also investigated. A sample of 55 undergraduate students with various background have participated in this study. The sample of students were asked to answer a set of questions with (post-test) and without (pre-test) using mySTATS Tracker. Then, the score obtained was recorded and analysed. Gap analysis and Independent t-test were applied in achieving the objectives of the study. The results showed that there was a significant difference in scores between pre-test and post-test, p < 0.05. It could be concluded that the users scored significantly higher and answered the questions in a significantly shorter time using mySTATS Tracker compared to without using it. The study also found that there was a significant difference in score based on gender and faculties, p < 0.05. Furthermore, there was a significant difference in the perception of the usefulness and effectiveness of this application based on respective faculties. In overall, mySTATS Tracker has received a positive feedback from the potential users. This study has proven that mySTATS Tracker is a good alternative solution in suggesting the right statistical analysis to the users.